The Human P5B-ATPase ATP13A2 is not a Ca2+ Transporting Pump - de Tezanos Pinto, Felicitas (2011)
The human gene ATP13A2 has been proposed to code for an ATP powered ion transporter of the P5B subfamily. Mutations of the human gene ATP13A2 were found to underlie an autosomal recessive form of early-onset parkinsonism (PD) with pyramidal degeneration and dementia. The ion transported by the ATP13A2 pump is not known, but several studies have shown that the P5-ATPases influence the homeostasis of intracellular Ca2+, and thus it has been suggested that they transport Ca2+. In order to evaluate this possibility Chinese hamster ovary (CHO) cells stably expressing the human ATP13A2 protein have been obtained and the Ca2+ transport activity of ATP13A2 was assessed by measuring the ATP-dependent uptake of Ca2+ into microsomal vesicles. As a positive control vesicles containing the human plasma membrane Ca2+ pump (PMCA) were used. No significant differences were found between vesicles containing the ATP13A2 protein and the control. Moreover, Ca2+ was unable to induce the formation of the P-ATPase acylphosphate intermediate in vesicles containing the expressed ATP13A2. These results favor the idea that the ATP13A2 does not transport Ca2+.